Antibacterial Efficacy of Sacrifical Anode Thin Films Combining Silver with Platinum Group Elements within a Bacteria‐Containing Human Plasma Clot. Issue 2 (18th September 2017) - Abuayyash, Adham; Ziegler, Nadine; Gessmann, Jan; Sengstock, Christina; Schildhauer, Thomas A.; Ludwig, Alfred; Köller, Manfred
Abstract : Silver (Ag) dots arrays (64 and 400 dots per mm 2 ) are fabricated on a continuous platinum (Pt), palladium (Pd), or iridium (Ir) thin film (sacrifical anode systems for Ag) and for comparison on titanium (Ti) film (non‐sacrifical anode system for Ag) by sputter deposition and photolithographic patterning. The samples are embedded within a tissue‐like plasma clot matrix containing Staphylococcus aureus (S. aureus), cultivated for 24 h. Bacterial growth is analyzed by fluorescence microscopy. Among platinum group sacrifical anode elements and a dense Ag sample, only the high Ag ion releasing Ag–Ir system is able to inhibit the bacterial growth within the adjacent plasma clot matrix. This study demonstrates that the antibacterial efficiency of Ag coatings is reduced under tissue‐like conditions. However, the new sacrificial anode based Ag–Ir system can overcome this limitation. Abstract : Sacrificial anode silver dot arrays, fabricated on continuous platinum, palladium, or iridium thin films by sputter deposition and photolithographic patterning are embedded within a tissue‐like plasma clot matrix containing growing Staphylococcus aureus . Among these samples or a dense Ag film, only the Ag–Ir dot array is able to inhibit the bacterial growth within the plasma clot matrix.